2015
DOI: 10.1038/bjc.2015.356
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival benefits of first-line EGFR tyrosine kinase inhibitors in EGFR-mutated non-small-cell lung cancers: a systematic review and meta-analysis

Abstract: Background:Accumulating data shows that exon 19 deletions and L858R, both activating epidermal growth factor receptor mutations in non-small-cell lung cancers (NSCLCs), are just two different entities in terms of prognosis and treatment response to tyrosine kinase inhibitors (TKIs).Methods:A systematic review and meta-analysis of randomized controlled trials comparing TKIs with conventional chemotherapy was performed. Eight trials of 1498 patients and five trials of 1279 patients with either exon 19 deletions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 47 publications
3
82
0
3
Order By: Relevance
“…Afatinib is hypothetically more effective at inhibiting EGFR signaling than reversible TKIs, due it forming stable covalent bonds and irreversibly inhibiting ATP from binding to the tyrosine kinase domain of EGFR (19); however, no randomized clinical trial or meta-analysis has demonstrated that afatinib is superior to erlotinib or gefitinib regarding OS. Irreversible TKIs have been reported to significantly improve the OS time of patients with exon 19 deletions (20,21). Despite such findings, the association between the expression of EGFR mRNA and protein and treatment response is currently unclear, as is the optimal method for determining EGFR levels in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Afatinib is hypothetically more effective at inhibiting EGFR signaling than reversible TKIs, due it forming stable covalent bonds and irreversibly inhibiting ATP from binding to the tyrosine kinase domain of EGFR (19); however, no randomized clinical trial or meta-analysis has demonstrated that afatinib is superior to erlotinib or gefitinib regarding OS. Irreversible TKIs have been reported to significantly improve the OS time of patients with exon 19 deletions (20,21). Despite such findings, the association between the expression of EGFR mRNA and protein and treatment response is currently unclear, as is the optimal method for determining EGFR levels in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, прием афатиниба в равной степени демонстрировал свое пре-имущество независимо от типа мутации гена EGFR: отно-сительный риск прогрессирования был снижен на 24% при Del19 и на 29% -при L858R. Однако в нескольких системных обзорах и метаанализах, а также в объединен-ном анализе результатов исследований LUX-Lung 3 и LUX-Lung 6 было показано, что подгрупповые мутации следует рассматривать как основной фактор, определяю-щий различие в биологических и клинических эффектах [35][36][37]. Что касается частоты объективного противоопу-холевого эффекта, то она составила 70% при назначении афатиниба и 56% при лечении гефитинибом (p = 0,008), при этом медиана продолжительности ремиссии состави- 4% и 3,1%), в то время как при приеме гефитиниба отмечена гепатотоксичность 3 ст.…”
Section: Oh (34-oh)unclassified
“…On the other hand, although the prevailing view is that of a favorable PFS and therapeutic responses to EGFR-TKIs in patients harboring Del19 compared with those harboring L858R, whether OS benefits from first-generation EGFR-TKIs are different between these 2 mutation types has remained controversial [9]. Data from the previous phase III trials suggest that the implementation of treatments before and after the first-generation EGFR-TKI therapy may have a positive impact on OS outcome [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of a series of reports, both Del19 and L858R, which are called “common mutations,” are considered to confer better therapeutic responses to EGFR-TKIs than other EGFR mutations, which are called “uncommon mutations” [7]. Furthermore, previous meta-analyses showed that EGFR-TKIs prolonged progression-free survival (PFS) in patients with tumors harboring Del19 compared with those harboring L858R [8,9,10]. EGFR-TKIs may therefore have the highest therapeutic impact on tumors harboring Del19 compared with tumors harboring other EGFR mutation subtypes.…”
Section: Introductionmentioning
confidence: 99%